Knowledge and behavior of Saudi University athletes toward energy and sport drinks with emphasis on microbial quality and safety - Aljaloud, Sulaiman Omar (Progress in Nutrition, 2020)
The aim of this study was to assess the knowledge and behavior of university athletes in Saudi Arabia toward energy and sports drinks. Also, the microbiological quality of local drinks available in the market was also assessed. Of the 120 university athletes surveyed, 69 were taking sports drinks, whereas 51 were taking energy drinks. The study consisted of ten questions related to the university athletes’ sociodemographic characteristics, personal habits, sports and energy drinks related knowledge, and habits. For the question related to the main reason for using energy drinks, results showed that 50.98% (n=26) believed that energy was the main reason for using energy drinks. On the other hand, 36.23% (n=25) believed recovery from injury or illnesses was the main reason for consumption of sports drinks. A majority of university athletes (n=43, 62.32%) who used SDs said they thought SDs were safe to use while n=22 (43.14%) were unaware of the safety of EDs. Total bacterial coliform, count, Escherichia coli, Salmonella, and Staphylococcus aureus were included in this analysis. Of the total of 26 tested sports and energy drinks, microbial contamination was present in only two products. Microbial levels and the total bacterial count for most of the samples were very low (